Earthworm Magic: Unlocking Kitchen Waste’s Potential through Vermicomposting - Prabjot Kaur (Innovations in Science and Technology: Shaping a Sustainable Future (Vol. 2), 2024)
Vermicomposting is a bio-conversion process of converting organic waste into a bio-fertilizer by the earthworm’s action. In this bioconversion method, earthworms feed on the organic waste, which may include vegetable or municipal waste, over a certain period of time and produce vermicompost; during the process, earthworms multiply twenty times a year. Earthworms most commonly used for vermicomposting include Eisenia Fetida, Eudrius Eugeniae and Eisenia Andrei. Vermicomposting can be carried out under any shady area that can be done under trees or it can be done in pits of sizes 10×3×2 feet. Regular monitoring and adjustments are necessary to maintain the right moisture content (about 70 %). Temperature control is crucial for successful vermicomposting. Extreme temperatures (too hot or too cold) can affect earthworm activity and decomposition rates. The typical range of temperature should be in the range of 18o to 35o C. It is a rich source of Nitrogen, Phosphorus and Potassium (NPK) and micronutrients. The NPK contents of vermicompost are higher than FYM (Farm Yard Manure), which is also called Black Gold. Vermicomposting is a very simple process of converting kitchen waste into vermicompost with the help of worms and, therefore can be adopted by any household people. It is an excellent way to manage kitchen waste and to keep the environment clean.